Micro-alloying with Mn in Zn–Mg alloy for future biodegradable metals application. (15th March 2016) - Liu, Xiwei; Sun, Jianke; Zhou, Feiyu; Yang, Yinghong; Chang, Rencao; Qiu, Kejin; Pu, Zhongjie; Li, Li; Zheng, Yufeng
Abstract: Zn as a novel biodegradable metal holds great potential in bioresorbable implant application since it possesses excellent biocompatibility and more corrosion resistant than Mg. In the present study, the effect of the micro-alloying element Mn on the Zn–Mg alloy was studied with mechanical properties, in vitro degradation behaviors and hemocompatibility being evaluated in comparison with pure Zn as control. The experimental Zn–Mg–Mn alloys were composed of the matrix Zn and secondary phase (MgZn2 ). Meanwhile, Zn–Mg–Mn alloys ingots exhibited much higher yield strength (YS), ultimate tensile strength (UTS) and hardness compared to pure Zn. But their elongation was reduced. The results of immersion in Hank's solution for 30 days revealed that the sequence of corrosion rates from high to low was: as-cast Zn–1Mg–0.1Mn alloy > as-cast Zn–1.5Mg–0.1Mn alloy > pure Zn. The consequences of electrochemical tests indicated that the calculated corrosion rates followed the ranking order: as-cast Zn–1Mg–0.1Mn alloy > as-cast Zn–1.5Mg–0.1Mn alloy > pure Zn. The results of hemolysis rate and platelet adhesion implied that the studied alloys had good blood compatibility. Furthermore, after hot-rolling, the YS, UTS, elongation and hardness of Zn–1Mg–0.1Mn alloys were further improved and possessed the superior mechanics performance (YS 195.02 MPa, UTS 299.04 MPa, Elongation 26.07%, Hardness 107.82 Hv), appropriate corrosion rate ( V corr 0.25 mm/year) and excellent hemocompatibility (hemolysis rate of 1.10% and no signs of thrombogenicity), showing the preferable candidate as a biodegradable implant material. Graphical abstract: Highlights: Micro-alloying with Mn in Zn–Mg biodegradable metal was fabricated and evaluated. The studied alloys showed higher YS, UTS, hardness and corrosion rate than pure Zn. Their elongation and hemolysis rates were reduced. Zn–1Mg–0.1Mn presented a potential in resorbable implant application after rolling.